CHARACTERISTICS OF RATIONALITY AND IRRATIONALITY IN THE SOCIAL ANTHROPOLOGY OF LOVE - Sultanova Nodira Ergashovna (International Journal of Innovations in Engineering Research and Technology, 2023)
In the article National-spiritual education: essence and principles. National and spiritual factors of raising children in the family. The role of national customs, traditions and traditions in educating the younger generation. The influence of the existing rules and regulations in the life of the people on the upbringing of a harmoniously developed generation in the family